Retrofitting and re-powering as a control strategies for curtailment of exposure of underground miners to diesel aerosols - Bugarski, Aleksandar D; Hummer, Jon A; Vanderslice, Shawn; Barone, Teresa (Mining, metallurgy & exploration, 2020)
A study was conducted to examine the potential of diesel emissions control strategies based on retrofitting existing power packages with exhaust aftertreatment devices and repowering with advanced power packages. The retrofit systems, a diesel oxidation catalyst (DOC) and diesel particulate filter (DPF), were evaluated individually using a US EPA tier 2 (ter 2) engine operated under four steady-state conditions and one transient cycle. The DOC effectively curtailed emissions of CO, and to some extent organic carbon (OC), elemental carbon (EC), and aerosol number concentration. The DPF system offered substantially higher reductions in OC and EC mass and aerosol number concentrations. Both, the DOC and DPF achieved reductions in the aforementioned emissions without adversely affecting emissions of NO and nano-sized aerosols. The strategy of repowering with an advanced system was examined using a US EPA tier 4 final (tier 4f) engine equipped with a cooled exhaust gas recirculation system and diesel exhaust fluid-based selective catalytic reduction system, but not with a DPF system. The tier 4f engine contributed substantially less than the tier 2 engine to the EC and OC mass, aerosol number, and CO, NO, and NO concentrations. The tier 4f engine was very effective in reducing aerosol mass, NO, and NO concentrations, but it was not equally effective in reducing aerosol number concentrations. The implementation of viable exhaust after treatment systems and advanced diesel power packages could be instrumental to the underground mining industry to secure a clean, economical, and dependable source of power for mobile equipment.